Incidence, risk factors, and clinical implications of enfortumab vedotin-related cutaneous toxicity in urothelial carcinoma: a large-scale, real-world study in Japan - Y. Kita; T. Hara; T. Kawahara; K. Hashimoto; Y. Matsushita; H. Ito; T. Abe; A. Igarashi; S. Shimura; T. Sazuka; A. Yokomizo; N. Takaoka; et al. (ESMO Real World Data and Digital Oncology)
Background: Enfortumab vedotin (EV), an innovative antibody–drug conjugate targeting Nectin-4, has emerged as a breakthrough therapy for locally advanced or metastatic urothelial carcinoma (la/mUC). However, EV-related cutaneous toxicity (EVRCT) remains a significant concern because of Nectin-4 expression in skin tissue. This study aimed to understand the incidence, risk factors, and clinical implications of EVRCT, focusing on relationships with treatment efficacy, using one of the largest real-world datasets from a Japanese la/mUC patient cohort. Materials and methods: Data from 207 la/mUC patients treated with EV, mainly as a third-line therapy between 2020 and 2023, were analyzed. Multivariate logistic regression and propensity score matching (PSM) were used to assess the risk factors and impact of EVRCTs on patient overall survival (OS) and progression-free survival (PFS). Results: EVRCTs were observed in 59.9% of patients, with 83% occurring within the first 3 months, defined as early-phase EVRCTs (epEVRCTs). Multivariate analysis identified better Eastern Cooperative Oncology Group performance status (ECOG PS = 0), higher hemoglobin levels (≥11 g/dl), and the standard initial dose (1.25 mg/kg) as significant risk factors for epEVRCTs. Patients with epEVRCTs demonstrated significantly improved PFS and OS compared with those without. Post-PSM analysis confirmed longer OS for patients with epEVRCTs, particularly those with mild (grade 1) toxicities, suggesting that these reactions may be significantly linked to favorable treatment outcomes. Conclusions: Our data suggest that epEVRCTs are common and correlate with better clinical outcomes in la/mUC patients treated with EV, underscoring the importance of proactive EVRCT management to optimize therapeutic benefits.